2012
DOI: 10.1051/mmnp/20127601
|View full text |Cite
|
Sign up to set email alerts
|

Delay Differential Equations and Autonomous Oscillations in Hematopoietic Stem Cell Dynamics Modeling

Abstract: Abstract. We illustrate the appearance of oscillating solutions in delay differential equations modeling hematopoietic stem cell dynamics. We focus on autonomous oscillations, arising as consequences of a destabilization of the system, for instance through a Hopf bifurcation. Models of hematopoietic stem cell dynamics are considered for their abilities to describe periodic hematological diseases, such as chronic myelogenous leukemia and cyclical neutropenia. After a review of delay models exhibiting oscillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…Time delays have been added to account for events such as cell divisions (for instance [12], [13]) and the interactions between cancer and immune cells (for instance [14]). In [13], Adimy and Crauste present three delay differential equation (DDE) models of cycling and quiescent hematopoietic stem cells (HSCs), with constant, distributed, and state-dependent delays. These delays represent the time to complete one cell division.…”
Section: Hematopoiesismentioning
confidence: 99%
See 2 more Smart Citations
“…Time delays have been added to account for events such as cell divisions (for instance [12], [13]) and the interactions between cancer and immune cells (for instance [14]). In [13], Adimy and Crauste present three delay differential equation (DDE) models of cycling and quiescent hematopoietic stem cells (HSCs), with constant, distributed, and state-dependent delays. These delays represent the time to complete one cell division.…”
Section: Hematopoiesismentioning
confidence: 99%
“…All three models have been applied to studying periodic hematological diseases, which are characterized by oscillations in various blood cell populations. It is concluded that although all three models produce periodic solutions, the nature of the oscillations depends on the type of delay [13]. …”
Section: Hematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the published works of the beginning of this decade are in the continuity of the end of the 2000's: cyclical neutropenia treatment by G-CSF [181], [182], [71], [94], [301], CML study [139], [158], [224], [106], [48], [178], [257], AML study [275], [274], [47], granulopoiesis [262], [263], HSC study [234], [207], [277], [33], [276], [281], [218], [5], [18], [136], [74] (with two nice reviews dealing with treatments of hematological diseases [96]), [294], very few on erythropoiesis [90], [261], [68] megakaryopoiesis [269], cell fate analysis [219]. There were mathematical development of structured populations [70], [111], [67], [114] with delay equations [20], [88], [21], [15], [59], [4], …”
Section: 'S: a Third Generation On Its Waymentioning
confidence: 99%
“…An intermediate approach is the use of delay differential equations (DDEs) models, which exhibit more complex dynamical behaviors (see, for example [2]). …”
Section: Introductionmentioning
confidence: 99%